Tintas anti-incrustantes de terceira geração: novos biocidas no ambiente aquático - Ítalo B. Castro; Eliete Westphal; Gilberto Fillmann (Química Nova, 2011)
Antifouling agents have been used on vessels and boats since ancient civilizations. Thus, a brief history on the three generations of antifouling paints was provided in the present review. Additionally, information about physic-chemical properties, environmental levels, toxicology and analytical methods was discussed for the 16 "new" booster biocides used as third-generation antifouling paints. The main problems, limitations and future trends related to this subject were also presented. Finally, actions were suggested in order to appraise the current status of the environmental impact caused by these compounds in South America.